Neoliberal and inclusive themes in European lifelong learning policy - Holford, John; Mohorčič Špolar, Vida A. (Policy Press, 2012)
DRAFT: not for citation. This is a pre-peer-review, pre-copy edited version of a chapter published in Sheila Riddell, Jörg Markowitsch, and Elisabet Weedon, eds., Lifelong learning in Europe: Equity and efficiency in the balance, Bristol: Policy Press (2012). Details of the definitive published version and how to purchase it are available online at: http://www.policypress.co.uk/display.asp?K=9781447300137&sf1=keyword&st1=riddell&m=1&dc=8